BEST PRACTICE IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (Studi Kasus Pelaksanaan Program Kemitraan dan Bina Lingkungan PT. Taman Wisata Candi (TWC) Borobudur, Prambanan dan Ratu Boko) - Arin Mamlakah Kalamika; Ahmad Khabiburohman (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
Social welfare can be achieved with cross-sectoral sectors,  covering the state, civil society, and the private sector (corporates). The private sector can help bring about social welfare through corporate social responsibility. Corporate Social Responsibility (CSR) as an empowerment development program. PT. Taman Wisata Candi (TWC) Borobudur, Prambanan, and Ratu Boko are one of the companies that handle CSR activities by uniting the partnership and community development program which is called by the term Program Kemintraan dan Bina Lingkungan (PKBL) and to be top CSR in the tourism category in 2018. This fact is researched to get the best practices of corporate responsibility social all this time. Using a descriptive qualitative research method, the study found a good implementation that is undoubtedly the three bottom-line effects in implementing CSR lead by PT. TWC. Keywords: CSR, Best Practices, Triple Bottom Line Effect.